Performance analysis of the RSS value for the video transmission using WiFi network / Hibatul Azizi Hisyam Ng - Hisyam Ng, Hibatul Azizi
Wifi coverage is frequently be an issues in any household with internet services subscriber. As to ensure user gain mobility when using the internet services, Wifi is consider as the best medium to be used in most premises be it in small houses like apartments until the spacious office floor area. In this paper, the studies continue to investigate the quality of Wifi coverage in average double story houses and how the Receive Signal Strength (RSS) value affects the performance of the services. From the study, we able to identify maximum acceptable RSS value from every type of respective bandwidth in DSSS and OFDM modulation.